The Influence of People, Physical Evidence and Process on Outpatient Satisfaction at Siti Fatimah Hospital, South Sumatra Province in 2023 - Intania Winalda; Innocentius Bernarto (Syntax Literate, 2022)
Medical services provided to patients are inseparable from their satisfaction with the medical services they receive. This study aims to examine and analyze the influence of the three elements of service, in the context of health services on patient satisfaction (Patient Satisfaction). The research method used is a quantitative research method with a survey where the data is obtained by cross sectional (Cross Sectional). The results model or empirical model from the PLS-SEM analysis shows that this research model has moderate predictive accuracy for the patient satisfaction variable. Patient satisfaction dependent variable can be explained by 60% by the three independent variables. From the new Cross Validated Predictive Ability Test (CVPAT) method, it is confirmed that this research model can be said to have predictive abilities. The findings of this study indicate that the three service element variables, namely People, Process and Physical Evidence, have strong evidence to say they can positively influence patient satisfaction in government-owned hospitals. The results of the IPMA statistical analysis show that the managerial implications that can be given are in the form of suggestions for the management of Siti Fatimah Hospital in South Sumatra Province to better manage services at the outpatient polyclinic. This can have an impact on service performance, because doctors are forced to examine patients quickly and often have to be in a hurry due to long queues of patients.